2x2+13x+6=0

Simple and best practice solution for 2x2+13x+6=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x2+13x+6=0 equation:



2x^2+13x+6=0
a = 2; b = 13; c = +6;
Δ = b2-4ac
Δ = 132-4·2·6
Δ = 121
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$\sqrt{\Delta}=\sqrt{121}=11$
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(13)-11}{2*2}=\frac{-24}{4} =-6 $
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(13)+11}{2*2}=\frac{-2}{4} =-1/2 $

See similar equations:

| 9-9n=-n-9-5n | | 5/6*w=7/18 | | 19=3(w+5)-5w | | 539=900-19w | | x/4-7=+ | | b^2-23b+132=0 | | x.5-4=-5 | | 7(x-1)=40 | | 3/8+k=7/8 | | 6x+33=3x+45 | | 5/4(20x+12)=54 | | 16-2(3x-1)=0 | | 4=20x/100 | | 10x+69=109 | | 6(6x+6)-5=6x | | g2–29g=0 | | 6r^2-72r+192=r | | x+9-9=839-9 | | -13(2*x)=13x-26 | | (7-3m)/(m^2-4)=0 | | x-9=830 | | 4c-8-6c=16 | | (x+36)+2x=90 | | 83f-51=51 | | x=32/4*2 | | x-9=8(21) | | 4.4-n=0.06 | | 6x+24-3x=9 | | 5^(6y)=2 | | 72c-72=-0 | | -339.12=18.84j | | 1=0.1x-0.7x-29 |

Equations solver categories